Curved directly glazed steel structure: New departure station, E‐Line, The Hague. Issue 4 (November 2016) - Helbig, Thorsten; Kamp, Florian; Schieber, Roman; Oppe, Matthias; Torsing, Rob; Kieft, Ralph
Abstract: ZJA Zwarts & Jansma Architects have designed a new light rail departure station in The Hague, The Netherlands. The spatial roof structure of the station is made of rolled steel rectangular hollow sections arranged in two independent layers rigidly connected to each other. A glass envelope covering the roof structure matches the contours of the steel exactly. Since the diamond‐shaped glass panes could only be attached to the outer layer of the steel grid, the panes (with edge lengths of approx. 1.30 m) are supported on two sides only. When optimizing the overall geometry, the double‐curvature area at the nose of the roof structure became a special focus. Knippers Helbig Advanced Engineering has managed to minimize the deviation of each single glass pane from the single‐curvature geometry to a maximum out‐of‐plane deformation of only 3 mm. Therefore, the project is a great example of how geometry development can influence structural design and enable new approaches.